Tindak Pidana Kasus Kekerasan Dalam Rumah Tangga (KDRT) dengan Istri sebagai Korban dan Penerapan Hukumnya di Pengadilan Negeri Sukoharjo - Sugiharto, Joko; Khasanah, Isrofiah Laela (CV. Kurnia Grup, 2024)
Domestic violence is a criminal act that must be firmly addressed. The household should be a safe place for its members as it is built upon the spiritual and physical bond between spouses. However, in reality, many households become sites of suffering and abuse due to acts of violence. The purpose of this study is to analyze the implementation of criminal provisions against cases of Domestic Violence with wives as victims, and to examine the obstacles in legal resolution of criminal acts of domestic violence with wives as victims, as well as efforts to resolve them. The research analysis indicates that law enforcement to enforce the Domestic Violence Elimination Act, which is laden with protections for victims' rights and their families, requires strong commitment and high respect for justice, non-discrimination, and human rights values as guaranteed by the constitution. Court decisions are expected to serve as a form of legal protection for victims' rights and to respond to the need to prevent the continuation of threats of domestic violence. Obstacles in the legal resolution of criminal acts of domestic violence include insufficient legal protection for victims, inadequate positive response from criminal justice personnel, underreporting or non-prosecution of domestic violence incidents, and lack of legal protection for victims. Efforts to resolve these issues include re-regulating domestic violence within legal provisions, training law enforcement officers on issues related to domestic violence, and public education to raise awareness of rights and roles in society.